2021
DOI: 10.3390/epidemiologia2030026
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Vaccination Strategy in Brazil—A Case Study

Abstract: Brazil is among the countries which have faced two devastating infection waves of COVID-19 in the past year. Despite the fact the country has one of the world’s leading immunization programs, Brazil only slowly established a national COVID-19 vaccination strategy and campaign. This case study is based on an integrative review of primary and secondary literature sources. Different search strategies on Medline and Google Scholar were performed for the case presentation, for the management and outcome of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…However, only 10% of people from low-income countries were vaccinated with one dose at that date. Even in largely vaccinated countries with severe inequalities, such as Brazil, there were areas with low vaccine coverage [ 51 ]. Additionally, vaccine hesitance and rejection spread in the developed world due to misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 10% of people from low-income countries were vaccinated with one dose at that date. Even in largely vaccinated countries with severe inequalities, such as Brazil, there were areas with low vaccine coverage [ 51 ]. Additionally, vaccine hesitance and rejection spread in the developed world due to misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that vaccination coverage for booster doses was incipient and had slow advancement in Brazil. Although the supply and availability of vaccines has progressively increased, vaccine hesitancy and the feeling of security by the population brought about by the rapid decrease in cases may be related to low adherence to booster doses [ 11 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, in May 2021, the population aged 18 to 59 began to be vaccinated according to the guidelines of the Brazilian NOP [ 19 ]. Subsequently, in June 2021 the vaccination of adolescents (12 to 17 years old) was started and in December 2021, children aged 5 to 11 years were also included for vaccination against Covid-19 in the country [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a multicentre cohort, involving several hospitals, from different cities in Brazil. It, also, includes the pandemic waves with different virulent strains of the virus, and the periods pre and post-vaccination for SARS-CoV-2 in Brazil [29].…”
Section: Discussionmentioning
confidence: 99%